(In)segurança alimentar e o uso de telas durante a pandemia do COVID-19 em famílias com crianças na primeira infância - Carneiro, Thaís Aquino (2022)
The growing use of screens by children and the food insecurity situation of many families have worsened with the pandemic. Family and child food insecurity rates are associated with adverse health and development conditions among young children. It is known that food plays a fundamental role, especially in the early years, which are decisive for growth and development. The objective of the study is to identify, together with families with children in early childhood, the situation of food (in)security and the association with screen time during the period of social isolation by COVID-19. Cross-sectional study, with the application of an online questionnaire with sociodemographic and health variables, a reduced Brazilian Food Insecurity Scale and the Questionnaire on the Family Use of Media Devices. Data collection took place virtually through a snowball, through a link shared by social networks such as Facebook®, Instagram and WhatsApp®, from September to December 2021 and comprised a sample of 417 participants. Data were tabulated and later statistical analysis and association of variables were performed in the Statistical Package for the Social Sciences version 20.0. The research project was approved under opinion 4,912,020/2021. The results show that mothers were the main caregivers, with an average age above 30 years, coming from Fortaleza, with a postgraduate degree, living with a partner and with an average family income of more than six minimum wages. Most families were identified with food security, however, those who lived in the countryside, with a low level of education (up to 1st/2nd grade) and with an income of up to 2.5 minimum wages were more likely to be food insecure. The children's average screen time exceeded the recommendations of the Brazilian Society of Pediatrics. There was statistical significance between screen time and food security, demonstrating that children who spend less screen time have more food security. It is concluded that this study can help nurses' knowledge of issues related to food safety and the main associated variables, including screen time, contributing to the monitoring of food (in)security and bringing evidence of actions aimed at promoting food safety. health of families of children in early childhood.